Unfazed by both the bull and bear: Strategic exploration in dynamic environments - Peter S. Riefer; Bradley C. Love (Games, 2015)
People in a changing environment must decide between exploiting options they currently favor and exploring alternative options that provide additional information about the state of the environment. For example, drivers must decide between purchasing gas at their currently favored station (i.e., exploit) or risk a fruitless trip to another station to evaluate whether the price has been lowered since the last visit. Previous laboratory studies on exploratory choice have found that people choose strategically and explore alternative options when it is more likely that the relative value of competing options has changed. Our study extends this work by considering how global trends (which affect all options equally) influence exploratory choice. For example, during an economic crisis, global gas prices may increase or decrease at all stations, yet consumers should still explore strategically to find the best option. Our research question is whether people can maintain effective exploration strategies in the presence of global trends that are irrelevant in that they do not affect the relative value of choice options. We find that people explore effectively irrespective of global trends.
Keywords: 330; decision-making; strategic choice; exploration and exploitation; dynamic environments; global trends